An Enhanced Nonlinear Hybrid Precoding Algorithm for Millimeter Wave Massive MIMO Systems. Issue 3 (April 2020) - Liu, Fulai; Zhang, Yanshuo; Du, Ruiyan
Abstract: Hybrid precoding has recently received considerable attentions in millimeter wave (mmWave) massive multiple-input multiple-output (MIMO) systems. Especially, a nonlinear hybrid Tomlinson-Harashima precoding (THP) algorithm has recently received considerable attentions since it can effectively improve the performance of the hybrid precoding. This paper presents an enhanced nonlinear hybrid Tomlinson-Harashima precoding algorithm based on the column-by-column refinement (named as E-THP-CR algorithm). Compared with the previous works, the proposed algorithm offers a numberof advantages.The advantageof the proposed algorithm lies in achieving the column-by-column refinement of the analog precoding matrix. Afterwards, the digital precoding matrix is decomposed into two separate sections which respectively belong to the encoding part and effective channel part. This design can effectively remove the inter-user interference as expected in the THP module. Simulation results verify that the proposed algorithm provides higher spectral efficiency, compared with the other relevant algorithms.